Data from: Annual ring growth of a widespread high-arctic shrub reflects past fluctuations in community-level plant biomass ... - Le Moullec, Mathilde; Buchwal, Agata; Van Der Wal, Rene; Sandal, Lisa; Hansen, Brage B. (Dryad, 2019)
1. Long time-series of primary production are rarely available, restricting our mechanistic understanding of vegetation and ecosystem dynamics under climate change. Dendrochronological tools are increasingly used instead, particularly in the Arctic – the world’s most rapidly warming biome. Yet, high-latitude plant species are subject to strong energy allocation trade-offs, and whether annual allocations to secondary growth (e.g. ‘tree-rings’) actually reflects primary production above-ground remains unknown. Taking advantage of a unique ground-based monitoring time-series of annual vascular plant biomass in high Arctic Svalbard (78N), we evaluated how well retrospective ring growth of the widespread dwarf shrub Salix polaris represents above-ground biomass production of vascular plants. 2. Using a balanced design in permanent plots for plant biomass monitoring, we collected 30 S. polaris shrubs across five sites in each of two habitats. We established annual ring growth time-series using linear mixed-effects ... : rwl_SemmeldalenCross-section raw ring-widths (micrometers) in format "Tucson". See the associated file "Shrub_Semmeldalen_info".Shrub_Semmeldalen_infoDescription of the individual cross-sections with a description of the column names in the second sheet of this document.Semmeldalen LME outputRing growth and above-ground biomass time-series obtained from linear mixed-effects models. See the description of the column names in the second sheet of this document. ...